Half-Fluence Photodynamic Therapy for Chronic Central Serous Chorioretinopathy: Predisposing Factors for Visual Acuity Outcomes - Matušková, Veronika; Vysloužilová, Daniela; Uher, Michal (Seminars in ophthalmology, 2018)
BACKGROUND: Central serous chorioretinopathy (CSC) is characterised by a serous detachment of the neurosensory retina in the macula. Chronic CSC tends to affect older individuals with a less favourable visual outcome. Photodynamic therapy (PDT) with verteporfin is a possible therapeutic approach in cases of CSC with no tendency for spontaneous resorption. PDT has shown good anatomic and functional results in treating chronic CSC. For the purpose of diminishing side effects, modifications of the standard protocol were used. MATERIALS AND METHODS: This is a retrospective study of 32 eyes with CSC of 32 patients treated by half-fluence PDT. The patients underwent complete ophthalmology examination. On optical coherence tomography (OCT) we measured central retinal thickness (CRT), the outer nuclear layer (ONL), presence of subfoveolar detachment of retinal pigment epithelium (PED), disturbance of external limiting membrane (ELM), morphological changes in the inner segment/outer segment (IS/OS) line and retinal pigment epithelium (RPE) atrophy. We evaluated at baseline, 3 and 12 months after PDT. RESULTS: The mean BCVA at baseline was 0.41 ± 0.23 log MAR, the mean BCVA at 3 months was 0.24 ± 0.20 and at the end of the follow-up it was 0.23 ± 0.200. We observed statistically significant improvements of visual acuity after 3 and 12 months (p < 0.001, Wilcoxon test). The mean central retinal thickness at baseline was 373 ± 87 µm, the mean CRT after 3 months was 234 ± 42 µm and after 12 months 223 ± 39 µm. A significant reduction from baseline was seen after 3 months and 12 months (p < 0.001, Wilcoxon test). Baseline ONL reached 80 ± 27 µm, after 3 months it was 78 ± 20 and after 12 months it was 74 ± 20 µm. We observed a statistically significant change in diminishing the amount of PED after PDT after 3 months and after 12 months (p = 0.021, McNemar's test). We observed that in patients with RPE ablation, there is lower chance for the restitution of the IS/OS layer (p = 0.045, Mann-Whitney test). We observed a negative association between the improvement of visual acuity after 12 months and the presence of RPE ablation (p = 0.031, Mann-Whitney test). Restitution of ELM was significantly more often in patients with shorter duration of symptoms, (p = 0.027 after 3 months, p = 0.033 after 12 months after PDT, Spearman correlation). Neither ocular nor systemic adverse effects were observed during the follow-up period. CONCLUSIONS: Half-fluence PDT treatment has shown to be a usually safe and often effective therapy in patients with chronic CSC. This study suggests that the most important predictive factor is baseline visual acuity. The important anatomical change detected using OCT is a thinning of the outer nuclear layer. Nonetheless, other studies with a larger number of patients and a longer follow-up are required.
Keywords: dospělí; Tomography, Optical Coherence; Female; Porphyrins; porfyriny; Adult; výsledek terapie; ženské pohlaví; optická koherentní tomografie; lidé; fundus oculi; Photochemotherapy; Photosensitizing Agents; Treatment Outcome; Central Serous Chorioretinopathy; následné studie; Fluorescein Angiography; Fundus Oculi; fotosenzibilizující látky; retinální pigmentový epitel; retrospektivní studie; Follow-Up Studies; Male; Aged; fluoresceinová angiografie; Retinal Pigment Epithelium; chronická nemoc; lidé středního věku; senioři; mužské pohlaví; zraková ostrost; Visual Acuity; fotochemoterapie; Chronic Disease; Retrospective Studies; Middle Aged; centrální serózní chorioretinopatie; Humans